TEACHING SPEAKING USING INSIDE-OUTSIDE CIRCLE METHOD FOR SENIOR HIGHSCHOOL STUDENTS - Evan Evan; Sitti Fatimah (Universitas Negeri Padang, 2018)
Speaking is an interactive process of constructing meaning that can involveproducing and receiving and processing information. it is very important productive skillin our daily life as a connector for each other. The purpose of this article is to explain how the implementation steps of this method in speaking lesson to senior high school student.IOC is a strategy to increase students' activeness in learning,it is suitable with the curriculum 2013, in that curriculum students must be active in the learning process. So, the writer chooses this method because IOC is a cooperative learning which students can learn together and more active in the class.